Overview: Global change effects on terrestrial biogeochemistry at the plant–soil interface - L. Fuchslueger; L. Fuchslueger; E. F. Solly; E. F. Solly; A. Canarini; A. Canarini; A. C. Brangarí; A. C. Brangarí (Biogeosciences, 2024)
“Global change” significantly alters organic matter and element cycling, but many of the underlying processes and consequences remain poorly understood. The interface of plants and soil plays a central role, coupling the atmosphere, hydrosphere, biosphere and lithosphere and integrating biological and geochemical processes. The contributions to this special issue address questions on both biotic and abiotic interactions underlying responses of terrestrial biogeochemical cycling to a range of global changes, including increases in atmospheric CO2 concentrations, warming, drought and altered water regimes. In this overview, we synthesize key findings of the contributing empirical, conceptual and modelling-based studies covering responses of plants to elevated CO2; the role of soil organisms in modulating responses to warming; impacts of global change on soil organic carbon, nitrogen, and mineral nutrient availability; and the influence of altered water-table depth caused by global change on greenhouse gas emissions. The showcased studies were conducted in regions from the Arctic to the tropics and highlight the manifold impacts of global change on various ecosystem components controlling biogeochemical processes occurring at the plant–soil interface. This multi-ecosystem interdisciplinary understanding is crucial for deciphering feedbacks of terrestrial ecosystems to the climate system.